Development of Decoupling Device for Vibration-Assisted Roller Polishing of Silicon Carbide Ceramics - Yan Gu; Ao Liu; Jieqiong Lin; Xiuyuan Chen; Faxiang Lu; En Sun (IEEE Access, 2020)
For the research of the performance of vibration-assisted roller polishing (VARP) on the silicon carbides (SiC), a new decoupling device was designed. By introducing the fully symmetrical structure and the double parallel four-bar mechanism, the movement in the X and Y directions is decoupled. The dynamic and static characteristics of the device are analyzed using finite element analysis. Testing experiments were conducted to investigate the actual performance of the developed device. The results show that the coupling rate of the x-axis and y-axis are about 1.6% and 1.4%, respectively. The working space of the device is about 38μm×42μm, and the natural inherent is about 1198Hz. In addition, a VARP force model for SiC was established to help scientifically understand the removal mechanism. The polishing experiments are carried out to verify the feasibility of the model and the effectiveness of the device. The experimental results show that the maximum error between the model results and the measured force is about 7.7%. As the amplitude and frequency of the device increase, the surface roughness of the SiC decreases from 168nm without vibration to 54nm and 47nm, respectively.